2021
DOI: 10.3390/w13172445
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Oxidation Processes Based on Sulfate Radicals for Wastewater Treatment: Research Trends

Abstract: In this work, the recent trends in the application of the sulfate radical-based advanced oxidation processes (SR-AOPs) for the treatment of wastewater polluted with emerging contaminants (ECs) and pathogenic load were systematically studied due to the high oxidizing power ascribed to these technologies. Additionally, because of the economic benefits and the synergies presented in terms of efficiency in ECs degradation and pathogen inactivation, the combination of the referred to AOPs and conventional treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(2 citation statements)
references
References 78 publications
(195 reference statements)
0
2
0
Order By: Relevance
“…As explained by Ao et al ( 2018 ) and Xia et al ( 2020 ), under pH < 7, the predominant radicals are , whereas above pH > 7, sulfate radicals are converted to –OH radicals by reacting with . At pH = 11, Urán-Duque et al ( 2021 ) observed a significant inhibition of the degradation process. Han et al ( 2020 a ) also used BiFeO 3 microsphere–activated (BFO) PMS to degrade diclofenac.…”
Section: Visible Light–driven Advanced Oxidation Processesmentioning
confidence: 97%
“…As explained by Ao et al ( 2018 ) and Xia et al ( 2020 ), under pH < 7, the predominant radicals are , whereas above pH > 7, sulfate radicals are converted to –OH radicals by reacting with . At pH = 11, Urán-Duque et al ( 2021 ) observed a significant inhibition of the degradation process. Han et al ( 2020 a ) also used BiFeO 3 microsphere–activated (BFO) PMS to degrade diclofenac.…”
Section: Visible Light–driven Advanced Oxidation Processesmentioning
confidence: 97%
“…The presence of metal ions like Fe­(II), Ag­(II), and Co­(II) in their reduced form can lead to other oxidation pathways . Reports are also available on sulfate radical-based oxidation paired with other AOPs, which have enhanced oxidation potential and increase the applicability to degrade a wide range of organic pollutants. , Figure summarizes the mechanisms involved in the degradation of organic pollutants by MOF-based SR-AOPs.…”
Section: Introductionmentioning
confidence: 99%